The association between 24-h blood pressure variability and major adverse cardiac events (MACE) in hospitalized patients with acute myocardial infarction: a retrospective cohort study - Harefa; Ika Prasetya Wijaya; Muhadi; Cleopas Martin Rumende; Sally Aman Nasution; Sukamto Koesnoe; Maruhum Bonar Marbun; Hamzah Shatri (The Egyptian Heart Journal, 2021)
Abstract Background Acute myocardial infarction (AMI) is major cardiovascular disease that causes high morbidity and mortality. In AMI, ischemia and necrosis affected some cardiomyocytes leading to a decrease in myocardial contractility which is followed by an acute proinflammation reaction and increased sympathetic tone. Meanwhile, high blood pressure variability (BPV) causing an increased left ventricular workload, heart rate, myocardial oxygen demand and induces proinflamations and endothelial dysfunction. Therefore a high BPV and its associated pathological effects are likely to aggravate the physiological function of the heart and affect the emergence of acute cardiac complications in AMI patients. This study aims to investigate the association’s between short-term BPV and major adverse cardiac events (MACE) in AMI patients. This retrospective cohort study used simple random sampling to identify AMI patients who were hospitalized at Cipto Mangunkusumo National Hospital between January 2018 and December 2019. Mann Withney was performed to investigate the association between BPV and MACE. Results The average systolic BPV value which was calculated as standard deviation (SD) and average real variability (ARV) was higher in the MACE group than in the non-MACE group. Systolic SD and systolic ARV in the MACE group were 13.28 ± 5.41 mmHg and 9.88 ± 3.81 mmHg respectively. In the non-MACE group, systolic SD and systolic ARV were 10.76 (4.59–26.17) mmHg and 8.65 (3.22–19.35) mmHg respectively. There was no significant association between BPV and MACE. However, there were significant differences between systolic SD and systolic ARV in patients with hypertension who experienced MACE and patients without hypertension who experienced MACE. Conclusions The BPV of AMI patients who experience MACE was higher than that of non-MACE AMI patients. There was no significant association between BPV ​​and MACE during the acute phase of AMI.